Clausenawallines G-K, carbazole alkaloids from Clausena wallichii twigs - Wisanu Maneerat (2018)
Five carbazole alkaloids, clausenawallines G-K (1-5), along with 12 known alkaloids (6-17) were isolated from the twigs of Clausena wallichii. Their structures were established using spectroscopic methods and the antibacterial activity of compounds 1-5 was evaluated. © 2013 Elsevier B.V. All rights reserved.